"\\cfrac{dz}{dy}=z \\cdot tan(y)+sin(y)\n\\\\ \\cfrac{dz}{dy}-z \\cdot tan(y)=sin(y)"
Then, when we compare the form to "\\cfrac{dz}{dy}+P \\cdot z=Q", we can identify that the integrating factor will be: "I=e^{\\int Pdy}=e^{-\\int tan(y)dy}=e^{\\ln(cos(y))}=cos(y)"
Then, we multiply the integrating factor I and proceed to solve the equation:
"\\\\ (cos(y))[\\cfrac{dz}{dy}-z \\cdot tan(y)]=sin(y)cos(y)\n\\\\ cos(y)\\cfrac{dz}{dy}-z \\cdot sin(y)=sin(y)cos(y)\n\\\\ \\cfrac{d}{dy}(z \\cdot cos(y))=sin(y)cos(y) \\iff d(z \\cdot cos(y))= sin(y)cos(y){dy}\n\\\\ \\int d(z \\cdot cos(y))=\\int sin(y)cos(y){dy}\n\\\\ z \\cdot cos(y)=-\\frac{1}{2} cos^2(y)+C"
We divide the last result by cos(y) to determine z:
"z =C\\cdot sec(y)-\\cfrac{1}{2} cos(y)"
Comments
Leave a comment